Tug-of-war between actomyosin-driven antagonistic forces determines the positioning symmetry in cell-sized confinement - Ryota Sakamoto (Nature Portfolio, 2020)
Symmetric or asymmetric positioning of intracellular structures such as the nucleus and mitotic spindle steers various biological processes. Here authors use an in vitro model and show that a tug-of-war between centripetal actomyosin waves and percolation of bulk actomyosin network direct the positioning.